Synthesis, characterization and molecular docking of hydroxyxanthone and renylated xanthone derivatives as potential aromatase inhibitor - Ramakrishnan, Shurutishria (2022)
Xanthone is an important scaffold for the development of new drugs due to its various positions and types of attached substituents with specific functions. This makes xanthone and their derivatives capable of exhibiting a variety of cytotoxic and biological activities. By discovering new lead compounds, the threats of existing and emerging diseases can be managed and synthesis is one of the most important approaches to this. This research project aimed to design and synthesize a series of xanthones with different types of attached substituents that were evaluated for their anti-cancer activity against breast cancer cell lines for their potential as aromatase inhibitors. These compounds were in vitro tested against breast cancer cell lines, MCF-7 and MDA-MB-231 cell lines which can lead to the discovery of new anticancer drug candidates for future drug discovery research. A total of twenty xanthones were synthesized where a series of hydroxyxanthone (45-52) were firstly prepared via modified Grover, Shah and Shah method, before further reacted with alkyl halide under reflux to obtain 3-O alkylated xanthone derivatives (53 and 54), while reacted with prenal to obtain prenylated xanthone derivatives (55-58) and then further reacted with alkyl halide to obtain alkylated prenylxanthone derivatives (59-64). The structures of synthesized xanthones were analyzed using spectroscopic methods such as Direct injection-mass spectroscopy (DI-MS), Fourier Transform Infrared (FTIR) and Nuclear Magnetic Resonance (NMR). Molecular docking studies were performed to study the binding affinity of these compounds (45-64) towards breast cancer enzyme, aromatase (PDB: 3EQM) . Based on the in vitro results, most of the compounds did not show any significant activity against the breast cancer cell lines except compounds 51 and 55 which showed moderate activity against the MCF-7 cell line with an IC50 value of 50±0.69 μM and 50±1.66 μM, respectively. However, only compound 51 showed moderate activity against the MDA-MB-231 cell line with an IC50 value of 60±0.67 μM, while compound 55 did not show any activity. These two compounds were then tested against VERO (African Green Monkey Kidney) and BEAS-2B (Lung Epithelial) cell lines to study their toxicity against normal cells. From the results obtained, compound 55 showed lesser toxicity against VERO and BEAS-2B cell lines with an IC50 value of 60±1.41 μM and 60±0.85 μM respectively, while compound 51 showed higher toxicity against normal cell VERO and BEAS-2B cell lines with an IC50 value of 35±1.51 μM and 40±0.70 μM compared to cancer cells. Hence, compounds 51 and 55 were chosen to study their binding interactions with aromatase (PDB ID: 3EQM), where the binding affinities of compounds 51 and 55 were -7.9 kcal/mol and -9.4 kcal/mol, respectively. Based on the results obtained, a series ofinteractions with the most of the amino acid residues in aromatase were involved incompound 51 and compound 55 which could play an important role in binding in thearomatase enzyme.